2018
DOI: 10.1186/s13063-018-2762-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of monomeric and oligomeric flavanols in the dietary management of patients with type 2 diabetes mellitus and microalbuminuria (FLAVA trial): study protocol for a randomized controlled trial

Abstract: BackgroundPatients with type 2 diabetes mellitus (T2D) are prone to micro- and macro-vascular complications. Monomeric and oligomeric flavanols (MOF) isolated from grape seeds (Vitis vinifera) have been linked to improved endothelial function and vascular health. The aim of this study is to determine the effect of a daily supplementation of 200 mg MOF on renal endothelial function of patients with T2D and microalbuminuria.Methods/designFor this double-blind, placebo-controlled, randomized, multicenter trial 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The FLAVA-trial was a double-blind, randomized controlled trial. The protocol of this trial has been published previously [28]. Adult patients with T2D and microalbuminuria were recruited between December 2014 and April 2019 from the outpatient diabetes clinics of four health care centers in Rotterdam, the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…The FLAVA-trial was a double-blind, randomized controlled trial. The protocol of this trial has been published previously [28]. Adult patients with T2D and microalbuminuria were recruited between December 2014 and April 2019 from the outpatient diabetes clinics of four health care centers in Rotterdam, the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting study carried out by Professor Rashid’s team of researchers [ 25 ] showed that monomeric and oligomeric flavanols isolated from grape seeds were able to improve the condition of patients with microalbuminuria and had a positive effect on renal endothelial function in patients with diabetes mellitus.…”
Section: Studies Related To Diabetes Mellitusmentioning
confidence: 99%